The ADA practical guide to substance use disorders and safe prescribing - O'Neil, Michael (Pharmacist); American Dental Association (Hoboken, New Jersey : Wiley Blackwell, 2015)
'This is in addition to a variety of legal regulations dentists must follow regarding the storage and record keeping of controlled substances'--Provided by publisher.
Machine generated contents note: Contributors xxxPreface xxxAcknowledgements xxx1. Substance Use Disorders, Drug Diversion and Pain Management- The Scope of the Problem / Michael O'Neil1. Introduction2. Definitions3. Overview: SUD, Drug Misuse, Drug diversion and Pain Managementa. SUDb. Medication Misusec. Alcoholismd. Drug Diversione. Pain Management in Dentistry4. Understanding the Cultures of SUD, Drug Misuse and Drug Diversiona. Sharing Cultureb. Income Driven Culturec. Substance Abuse Cultured. Addiction Culturee. Combination of Cultures5. Summary2. Understanding the Disease of Substance Use Disorder / Carl Rollynn Sullivan and James Berry1. Introduction2. Definitions3. Epidemiology: Drug / Alcohol4. Pathophysiology5. Signs /Symptoms/ Behaviora. alcoholb. benzodiazepinesc. opioidsd. stimulantse. cannabisf. nicotineg. hallucinogens, designer drugs, inhalants6. Treatment methodsa. Behavior modification and counseling1. Motivational Interviewing2. CBT3. Contingency Management4. AA / 12 stepsb. Pharmacological management(Agents, pharmacology, pharmacokinetics, dosing, adverse effects, contraindications, drug selection, goals, duration of treatment, monitoring, outcome documentation)7. Summary3. Principles of Pain Management in Dentistry / Paul Moore and Elliot Hersh1. Introduction2. Definitions3. Neurophysiology and Neuroanatomy of Acute Inflammatory Pain4. Agents, pharmacology, pharmacokinetics, dosing, adverse effects, contraindications, Drug selection, duration of treatment, monitoring, documentationa. nonopioidb. opioid5. Medication Assisted Therapies for Drug Dependence6. Adjunctive Drugs7. Preemptive Analgesics8. Corticosteroids9. Guidelines to Analgesic Therapy10. Summary5. Special populations (renal insufficiency, coagulopathies, etc.)6. Safe prescribing considerations7. Summary4. Special Pain Management ConsiderationsMichael O'Neil1. Introduction2. Definitions3. Interviewing the Patient: Establishing Goals of Treatment4. Pharmacological Treatment of Opioid Addiction / Acute Paina. methadoneb. buprenorphinec. naltrexone5. Acute pain management patients with chronic nonmalignant pain6. Summary5. Sedation and Anxiolysis / Matthew Cooke1. Introduction2. Definitions3. Spectrum of Anesthesia and Sedation4. Preoperative evaluation5. Physical Status Classification6. Sedation7. Medications in Patients with SUDa. nitrous oxideb. benzodiazepinesc. opioidsd. ketaminee. propofolf. alpha-agonistg. local anesthetics8. Balance Anesthesia9. Monitoring and documentation10. Moderate conscious sedation11. Deep sedation12. Emergencies13. Special considerations14. Summary6. Common Substances and Medications of Abuse / George Raymond and William Maloney1. Introduction2. Definitions3. Signs and symptoms4. (drugs/chemicals, pharmacology, effects, routes, dental characteristics/patho, disease specific complications)a. Illicit drugs1. Stimulants -- Methamphetamine, Cocaine2. Hallucinogens3. Opioids4. Inhalants5. CNS depressants6. Marijuana5. Prescription Drugs1. Opioids2. Stimulants3. CNS depressants4. Antipsychotics5. Muscle relaxants6. Anticonvulsants7. Other Agents6. OTCs7. Summary7. Nicotine and tobacco Cessation / Frank Vitale and Amanda Eades1. Introduction2. Definitions3. Epidemiology -cigarettes, cigars, pipes, water pipes, chewing tobacco, dip/snuff4. Oral effects of tobacco5. Dental practitioner Management of Tobacco USEa. Brief interventionb. Low intensityc. Moderate intensityd. Spit tobacco interventions6. Medication Managementa. Role of nicotineb. NRTc. Individual Agentsd. Non FDA approved treatments7. Summary8. Detection and Deterrence of Substance Use Disorder and Drug Diversion in Dental Practice / Sarah Melton and Ralph Orr1. Introduction2. Definitions3. Screening patients and referrals for treatment/interventiona. SBIRTb. CAGEc. NMASSIST4. Schemes and scamsa. In office behaviorsb. Behavior preventionc. Out of office behaviorsd. Dental practitioner Diversion5. PDMPa. Brief History of PDMPsb. PDMP as a tool / general principlesc. Interpreting PDMP reportsd. Case6. Drug disposal7. Universal Safe prescribing practices9. Summary9. Dentist Interviewing and Counseling of Patients with Substance Use Disorders and Dealing with Drug Seeking Patients / George Raymond and William Maloney1. Introduction2. Definitions3. Pre-interview considerations4. Questions to ask5. Interviewing / counseling6. Screening tools7. Documentation8. Summary10. Office Management of Controlled Substances and Record Keeping / Carlos Aquino1. Introduction2. Definitions3. Federal and State Regulations4. Common violations by dentista. Scope of practiceb. Record keepingc. Storaged. Record keeping5. Record Keepinga. Purchasing / storage /securityb. Drug disposal6. Documentation7. Surviving a Dental Board Inspection or DEA Audit8. Due Diligence9. Non-Controlled Substance Management10. Summary11. The Impaired Dental Health Professional and Office Staff / William Kane1. Introduction2. Definitions3. Epidemiology of Substance Use Disorder in healthcare4. Neurobiology5. Stigma of Addiction6. Risk Factors7. Substances of Choice8. Identification of the Impaired Professional9. Interventions10. Treatment11. Well-being Committees12. Summary12. Due Diligence and Safe Prescribing / Michael O'Neil1. Introduction2. Definitions3. Case Scenarios A-J4. SummaryContinuing Education Questions, xxxIndex xxx.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Dental care -- United States; Substance abuse -- United States; Dental offices -- United States -- Organization; Dentist and patient -- United States; Drugs -- Prescribing -- Law and legislation -- United States; Drug control -- United States; Dental Care; Substance-Related Disorders; Dental Offices -- organization & administration; Dentist-Patient Relations; Drug Prescriptions -- standards; Drug and Narcotic Control; United States; Medical; MEDICAL -- Surgery -- General; Electronic books; Electronic books